Democratic Values, Pedagogy and Henry Giroux - Devkota, Mahadev (Madhyabindu Journal, 2021)
The present study "Democratic values, pedagogy and Henry Giroux” is an attempt to explore the democratic values in the pedagogy particularly in critical pedagogy in regard to Henry Giroux's perspective. This qualitative research employed descriptive methodology along with using relevant secondary sources for the claim, supporting reasons, and finally develop argumentation based on themes since it is written in the form of argumentation. The finding of this study shows that critical pedagogy as a wider democratic project plays an amicable role to impart democratic values across the country including the classroom practices. However, this relatively new paradigm is also not free from criticism. It is criticized as impractical, misleading and conflict-oriented rather than actually solving the problem.